Trauma-Informed Mental Health: Supporting Young People Involved With Child Protection Services - Appleby, Jo (Taylor and Francis Group, 2025)
Reported in this article are research findings about effective mental health practices for young people involved with child protection services. Five care-experienced young people and 45 stakeholders were interviewed to gather stories of effective mental health practice in Aotearoa New Zealand. The results illustrated what trauma-informed practice can look like throughout the mental health engagement, assessment, and intervention stages. The foundation of trauma-informed mental health care for this population is a deep understanding of the impact of trauma upon young people, recognition of care-experienced young people as a priority population, and a commitment from mental health services to responsively serve these young people. IMPLICATIONS Well-resourced specialised trauma-informed mental health care is important for young people who have been involved with child protection services, many of whom face inequitable barriers in accessing quality mental health care. Trauma-informed clinicians, including social workers, recognise trauma responses as adaptive behaviours rather than a reason to decline mental health service provision. Trauma-informed mental health interventions are based on principles of choice and predictability. Systemic trauma-informed care aligns with critical social work perspectives and antioppressive practice.
Keywords: 4409 Social Work; 44 Human Society; Health Services; Clinical Research; 8.1 Organisation and delivery of services; 7.1 Individual care needs; Mental health; 3 Good Health and Well Being; 1303 Specialist Studies in Education; 1605 Policy and Administration; 1607 Social Work; Social Work; 4407 Policy and administration; 4409 Social work; Youth; Mental Health; Child Protection; Out-Of-Home Care; Care-Experienced Young People; Trauma; Social Work; New Zealand